Self-compassion and the impostor phenomenon: Associations and implications - Kristýna Krejčová; Lucie Kvasničková Stanislavská; Fabio Ibrahim (PLoS ONE, 2026)
Impostor phenomenon reflects persistent self-doubt and fear of failure despite success. This study examined the association of impostor phenomenon with self-compassion in 601 Czech university students (368 women; M age = 23.46, SD = 3.05), using the Impostor-Profile 30 and Self-Compassion Scale. Employing correlation analysis, regression, and structural equation modelling, we investigated the relationships among the constructs and their dimensions. In the correlation analysis, competence doubt was moderately associated with isolation ( r = .409) and overidentification ( r = .427). The regression analysis indicated these subscales as being significantly associated with competence doubt (R² = .26, F(6, 594) = 35.18, p < .001). Structural equation modelling further supported the model with stronger links between negative self-compassion dimensions and impostor phenomenon compared with positive ones (e.g., self-kindness) (CFI = .99, TLI = .99, RMSEA = .031). These findings highlight the importance of considering feelings of isolation and overidentification when designing or interpreting self-compassion-focused approaches in the context of impostor phenomenon, particularly among university student populations vulnerable to stress and low self-efficacy.